Effect of Emotional Intelligence on Organisational Commitment in Higher Educational Institutions in Haryana - KUMAR, DINESH; RAM, TIKA; PAL, SHISH (The journal of contemporary issues in business and government, 2021)
The objective of the paper is to explore the relationship between emotional intelligence and organisational commitment among the employees of the higher educational institutions in Haryana. A structured questionnaire is used to assess emotional intelligence and organisational commitment. Participants of the study included 350 employees working in higher education institutions in Haryana, India. Confirmatory factor analysis is used to validate the scales and structural equation modeling is used to explore the relationship between emotional intelligence and organisational commitment using AMOS 21. It is concluded that emotional intelligence is positively associated with organisational commitment. Employees with strong emotional intelligence have greater levels of organisational commitment.